(untitled) (GAIMS Journal of Medical Sciences, 2024)
Background: This study aims to identify factors influencing medical students’ academic performance and develop a simplified action plan to prevent academic failure. Materials and Methods: A prospective educational intervention utilized Ron Fry’s Questionnaire to assess seven performance factors (concentration, comprehension, test anxiety, organizational skills, writing skills, computer skills, and system of taking notes in class) among medical students. Standard solutions with individualized action plans including intention statements, constant reminders, identifying reasons for test anxiety, and organizing oneself were offered based on these factors to create individualized action plans. Pre- and post-study test scores were compared using paired T-tests, and feedback was collected. Results: A total of 117 students participated, showing significant improvement in post-study marks (p = 0.00015). 31.6% of students improved and avoided failure post-study. 99% of students believed such interventions could benefit future batches in early performance identification. Conclusions: Utilizing Ron Fry’s questionnaire to identify performance factors and offering support in the form of standard solutions, may collectively enhance academic performance and reduce academic failure.